Joint and Separate Detection-Decoding on BPMR Channels - Wu, Tong; Armand, Marc A. (IEEE transactions on magnetics, 2013)
The presence of written-in errors is recognized as a challenging issue that limits the performance of bit-patterned media recording (BPMR). In this paper, we consider the Davey-MacKay coding scheme for a BPMR channel model which consists of a write channel producing dependent insertion, deletion, and substitution errors and a single-track equalized read channel with a GPR target. Three detection-decoding algorithms are proposed to work with an outer LDPC decoder to recover data encoded by the DM coding scheme on the BPMR channel. These include the Bahl-Cocke-Jelinek-Raviv binary input inner decoder (BCJR-BIID) algorithm, the joint detection-decoding algorithm and the separate detection-decoding (SDD) algorithm. Computer simulations show that at low to moderate (resp. high) signal-to-noise ratios, SDD (resp. BCJR-BIID) provides good performance-complexity trade-offs.